(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Jayapura City is a malaria-endemic area, with Kayo Batu Village as one of the villages in Jayapura City, which has an endemic level III or API > 100%. The highest of APIs are influenced by an imbalance of host, agent, and environmental factors, such as low levels of malaria prevention behavior and lack of environmental control. This service activity aims to carry out early detection of malaria, which is expected to be a step in preventing malaria transmission to reduce morbidity and death rates due to malaria. The activity method was carried out by mass blood examination (Mass Blood Survey) using the Rapid Diagnostic Test (RDT) on 164 residents in three RT Kampung Kayo Batu. Inspections are carried by door to door. There were three people (1.8%) who tested positive for malaria with the Plasmodium falciparum parasite type. Of the three people who tested positive for malaria, two people were children aged 6-11 years, and one person was an adult. There is a need to increase the knowledge, skills, and awareness of the people of Kampung Kayu Batu regarding preventing malaria by routinely eradicating mosquito nests around the house to reduce the number of malaria infections. It is hoped that all parties will increase awareness of malaria and encourage behavioral changes toward malaria prevention and environmental control.